Pancreatic cancer and exosomes: role in progression, diagnosis, monitoring, and treatment - Fang, Xingliang; Lan, Huanrong; Jin, Ketao; Qian, Jun (Frontiers in Oncology, 2023)
Pancreatic cancer (PC) is one of the most dangerous diseases that threaten human life, and investigating the details affecting its progression or regression is particularly important. Exosomes are one of the derivatives produced from different cells, including tumor cells and other cells such as Tregs, M2 macrophages, and MDSCs, and can help tumor growth. These exosomes perform their actions by affecting the cells in the tumor microenvironment, such as pancreatic stellate cells (PSCs) that produce extracellular matrix (ECM) components and immune cells that are responsible for killing tumor cells. It has also been shown that pancreatic cancer cells (PCCs) derived exosomes in different stages carry molecules. Checking these molecules' presence in blood and other body fluids can help us in the early stage diagnosis and monitoring of PC. However, immune system cells-derived exosomes (IEXs) and mesenchymal stem cells (MSCs) derived exosomes can contribute to PC treatment. Immune cells produce exosomes as part of the mechanisms involved in the immune surveillance and tumor cell-killing phenomenon. Exosomes can be modified in such a way that their anti-tumor properties are enhanced. One of these methods is drug loading in exosomes, which can significantly increase the effectiveness of chemotherapy drugs. In general, exosomes form a complex intercellular communication network that plays a role in developing, progressing, diagnosing, monitoring, and treating pancreatic cancer.